2016
DOI: 10.1080/13632752.2015.1120055
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and synthesis of qualitative research: the influence of school context on symptoms of attention deficit hyperactivity disorder

Abstract: (word count: 150) This systematic review and synthesis of qualitative research explored contextual factors relevant to non-pharmacological interventions for Attention Deficit Hyperactivity Disorder (ADHD) in schools. We conducted meta-ethnography to synthesise 34 studies, using theories of stigma to further develop the synthesis. Studies suggested that the classroom context requiring pupils to sit still, be quiet and concentrate could trigger symptoms of ADHD, and that symptoms could then be exacerbated thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 46 publications
2
33
0
5
Order By: Relevance
“…Delivery of interventions in the classroom avoids issues of stigma, strain on peer relationships and, of particular relevance to academic outcomes, mean that children in regular education miss less curriculum content. Other previous work stresses the importance of self-regulation as a key challenge for children with ADHD in school settings (Barkley, 1997;Gwernan-Jones et al, 2015a). Furthermore, Purdie et al (2002) reported strong effects for self-regulation interventions both in and out of school settings for children with ADHD.…”
Section: Relation To Previous Literaturementioning
confidence: 89%
See 3 more Smart Citations
“…Delivery of interventions in the classroom avoids issues of stigma, strain on peer relationships and, of particular relevance to academic outcomes, mean that children in regular education miss less curriculum content. Other previous work stresses the importance of self-regulation as a key challenge for children with ADHD in school settings (Barkley, 1997;Gwernan-Jones et al, 2015a). Furthermore, Purdie et al (2002) reported strong effects for self-regulation interventions both in and out of school settings for children with ADHD.…”
Section: Relation To Previous Literaturementioning
confidence: 89%
“…As the vast majority of children in the UK are in mainstream school settings, challenging behaviour arising from the difficulties associated with ADHD can cause problems in the classroom, for the child, the teacher and for other children (Abikoff et al, 2002;Greene et al, 2002). The classroom context, as well as teachers' attitudes and behaviour towards children with ADHD, impact on children's outcomes (Sherman et al, 2008;Gwernan-Jones et al, 2015a). The nature of the school setting in the UK, where children are often taught by one teacher, in large seated groups, is clearly at odds with the challenges experienced by children with ADHD in the domains of social and peer interactions, regulation of impulsive behaviour and verbal expression, and difficulty keeping on task and focussing attention.…”
Section: School-related Difficultiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Data on sample, study details, research methods and findings were extracted using a checklist adapted from a recent systematic review (Gwernan‐Jones et al., ) by AP and checked by MA.…”
Section: Methodsmentioning
confidence: 99%